Humanities and Religious Studies: Reflections on the Future - Atkinson, David W (Religious Studies and Theology, 2020)
There is particular angst expressed today about the future of the Humanities, although this concern has been with us for a long time. Many are concerned that the Humanities are dying and no longer occupy a position of importance in our universities. While there is every reason to be concerned, there has never been a time when the Humanities are more important. The Humanities must no longer accept a position at the periphery of universities and must, instead, assert their centrality. Religious Studies, as a relatively new Humanities discipline, offers a path forward. It suggests an openness that serves as a paradigm for the Humanities with regard to how to look outside themselves for new ways of doing research and teaching their students.